2002
DOI: 10.1248/yakushi.122.407
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Bile Hydrogen Peroxide Level and Liver Super Oxide Dismutase Activity in Selenium-Deficient Rats

Abstract: The relationship of hydrogen peroxide (H 2 O 2 ) levels in bile with liver SOD and GSH Px activity in selenium (Se)-deˆcient rats is discussed. Normal rats and 7 groups of rats fed a Se-deˆcient diet with diŠerent feeding periods were examined. H 2 O 2 levels in bile were measured using the spin-trapping method with electron spin resonance (ESR). Bile H 2 O 2 levels in the initial stage (20 60 min from start of the cannulation) of measurement were increased depending on the length of the feeding period with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
3
5
0
Order By: Relevance
“…We also observed that when the Se-GPx activity decreases, an SOD activation occurs in the selenium-depleted animals. The same results were published by Matsumoto et al 37 for selenium-deficient rats. This SOD activation might be related to the deficiency of the GPx activity, underlying a compensatory mechanism that is worth studying.…”
Section: Discussionsupporting
confidence: 87%
“…We also observed that when the Se-GPx activity decreases, an SOD activation occurs in the selenium-depleted animals. The same results were published by Matsumoto et al 37 for selenium-deficient rats. This SOD activation might be related to the deficiency of the GPx activity, underlying a compensatory mechanism that is worth studying.…”
Section: Discussionsupporting
confidence: 87%
“…Which cytochrome P-450 may be induced is under investigation. Regular purchasable Wistar rats were used as a control of comparison with the SeD rats in a series of our reports [3][4][5][6][7][8]16], although the SeD diet supplemented with Se should be used as a control. Se contents in the normal diet (CE-2, CLEA Japan, Tokyo, Japan) and the SeD diet (Oriental Yeast) were 0.86F0.03 and 0.017F0.002 mg/kg (meanFS.D.…”
Section: Discussionmentioning
confidence: 99%
“…Se in mammals is in, primarily, glutathione peroxidase (GSH-Px), which reduces hydrogen peroxide (H 2 O 2 ) using glutathione (GSH) as the cofactor. Feeding rat on a Se-deficient (SeD) diet reduces tissues' Se levels, notably in liver, in accordance with the Se contents of the diet [2] and/or the feeding period [3]. Selenium-deficient diet results in decreased GSH-Px activity and oxidative stress due to the increasing level of tissues' H 2 O 2 [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, when oxidative stress occurred, the activities of SOD and CAT in gills of zebra sh signi cantly dropped (Jin et al 2015). Analogous results were also found in mice liver and spleen (Meng et al 2004;Matsumoto et al 2002). Not only that, oxidative stress accounted for reduces in GPX activities of gills and livers in black porgy (Chen et al 2009), as well as in spleen of zebra sh (Komoike and Matsuoka 2013).…”
Section: Discussionmentioning
confidence: 83%